Structural observation of the primary isomerization in vision with femtosecond-stimulated Raman. - Kukura, P; McCamant, D; Yoon, S; Wandschneider, D; Mathies, R (2005)
The primary event that initiates vision is the light-induced 11-cis to all-trans isomerization of retinal in the visual pigment rhodopsin. Despite decades of study with the traditional tools of chemical reaction dynamics, both the timing and nature of the atomic motions that lead to photoproduct production remain unknown. We used femtosecond-stimulated Raman spectroscopy to obtain time-resolved vibrational spectra of the molecular structures formed along the reaction coordinate. The spectral evolution of the vibrational features from 200 femtoseconds to 1 picosecond after photon absorption reveals the temporal sequencing of the geometric changes in the retinal backbone that activate this receptor.